The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4103/1008-682x.125911
|View full text |Cite
|
Sign up to set email alerts
|

Male accessory gland inflammation prevalence in type 2 diabetic patients with symptoms possibly reflecting autonomic neuropathy

Abstract: Male accessory gland inflammation or infection (MAGI) is a potentially underdiagnosed complication of type 2 diabetes (DM2); specifically, we reported in a recent study that the frequency of MAGI was 43% among DM2 patients. In previous studies, we have demonstrated that diabetic autonomic neuropathy (DAN) is associated with a peculiar ultrasound characterization of the seminal vesicles (SVs) in DM2 patients. The aim of the present study was to evaluate the frequency of MAGI in two different categories of DM2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
1
4
0
Order By: Relevance
“…The authors suggested that hypogonadism plays a critical role in the development of prostate inflammation [ 39 , 43 ]. Together with other results, this indicates that, in patients with both hypogonadism and prostate inflammation, TRT may alleviate inflammatory changes and prevent the development of BPH or LUTS [ 3 , 39 , 57 , 58 ]. Fig.…”
Section: Testes Prostate and Androgenssupporting
confidence: 72%
“…The authors suggested that hypogonadism plays a critical role in the development of prostate inflammation [ 39 , 43 ]. Together with other results, this indicates that, in patients with both hypogonadism and prostate inflammation, TRT may alleviate inflammatory changes and prevent the development of BPH or LUTS [ 3 , 39 , 57 , 58 ]. Fig.…”
Section: Testes Prostate and Androgenssupporting
confidence: 72%
“…Similar considerations should also be applied to the epididymal US feature, since signs of inflammation or neuropathy on US have been revealed to promote the diagnosis [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, scientific interest for the potential male reproductive consequences of diabetes mellitus (DM) has been growing [1]. The greatest attention has been given to patients with type 2 DM (DM2), mainly because of its greater prevalence and clearer pathogenic mechanisms (hypogonadism, oxidative stress, neuropathy, sexual dysfunction) [1,2,3,4]. However, data concerning sperm quality also emerge in type 1 DM (DM1) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 40% of men with diabetes may complain of ejaculatory dysfunction[ 99 ]. Of these PE, DE, AE, and RE are the most common and the focus of this discussion[ 100 - 113 ].…”
Section: Diabetes-related Ejaculatory Dysfunctionsmentioning
confidence: 99%